2022
DOI: 10.3389/fpsyg.2022.1028264
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influencing factors and the functioning mechanism of online learning supporting learners’ empowerment

Abstract: The construction of an effective technology-based environment to promote learning and enable online learning to truly empower learners has become an increasingly important issue of concern. To some extent, an in-depth analysis of the key influencing factors and their functioning mechanism of online learning supporting learners’ empowerment may pave a new way for the understanding of this issue. In view of this, this study, grounded on the reciprocal determinism theory, explored the influencing paths among envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Learners’ experiences of online learning differ from those of face-to-face learning mainly due to a fundamental difference in the learning environment where learning takes place. Hence, previous studies on online learning have focused on the online learning environment that included factors such as the teacher’s teaching ability, curriculum design, and network support ( Zhu et al, 2022 ), as well as the learning situation, learning activities, and teaching design ( Pan, 2022 ). Specifically, Zhu et al (2022) investigated the relationships among learning behavior, learning cognition, and learning environment in an online setting and found that the online learning environment positively impacted online learning behavior.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners’ experiences of online learning differ from those of face-to-face learning mainly due to a fundamental difference in the learning environment where learning takes place. Hence, previous studies on online learning have focused on the online learning environment that included factors such as the teacher’s teaching ability, curriculum design, and network support ( Zhu et al, 2022 ), as well as the learning situation, learning activities, and teaching design ( Pan, 2022 ). Specifically, Zhu et al (2022) investigated the relationships among learning behavior, learning cognition, and learning environment in an online setting and found that the online learning environment positively impacted online learning behavior.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Specifically, Zhu et al (2022) investigated the relationships among learning behavior, learning cognition, and learning environment in an online setting and found that the online learning environment positively impacted online learning behavior. Pan (2022) also examined the online environment as one of the factors that has a positive influence on learners’ empowerment. The quality of learning experiences in an online environment was also associated with external factors such as network services or access to mobile devices ( Bast, 2021 ; Sarkar et al, 2021 ).…”
Section: Previous Studiesmentioning
confidence: 99%
“…From the literature, learners’ empowerment “was described in terms of two key dimensions: (1) value identification, which focuses on learners’ identity to the meaning and value of learning in relation to one’s own beliefs, ideals, and standards; and (2) self-reinforcement, which refers to learners’ engaging in self-fulfilling behaviors in relation to the individual’s perception of their own learning capability” (Pan, 2022b, p. 3). Taking into account the evidence that, in the online learning environment, the multi-faceted and multi-sensory feelings of the individual learners in technology-based learning constitute the unique emotional experience and form learners’ understanding of the “empowerment” of technological applications, this study extended the conception of learners’ empowerment by adding a new dimension of affective state which describes a cognitive belief state of personal involvement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following on from this, Zimmerman (2000) highlighted that the potential for empowerment lay in individuals' possessing the opportunity to take initiative, make choices, participate in decision-making and connect to their communities. Grounded on Frymier et al (1996)'s study, Pan (2022b) put forth that ''in the field of education, learners' empowerment refers to the process by which learners accomplish tasks, improve self-efficacy and develop multiple capabilities in specific learning situations and activities, which concentrates on the transformation of learners' thinking, the process of identifying with task values, and the reinforcement of self-meaningful behaviors, thus making individual and collective goals consistent so as to ultimately promote the realization of collective goal'' (p. 3). Indeed, learners need to be empowered to develop themselves as responsible individuals in the process of self-fulfillment.…”
Section: Learners' Empowermentmentioning
confidence: 99%
See 1 more Smart Citation